Decade-Long Insights into Soil Microbial Activity and Organic Carbon Derived from Crop Diversity - Judith L. Ronco; Cecilia Crespo; Lucila Bassi; Susana Perelman; Juan P. Martínez; Nicolás Wyngaard; Fernanda Covacevich; Pablo Barbieri (Journal of Soil Science and Plant Nutrition, 2025)

First fatal HPAIV H5N1 (Clade 2.3.4.4B) infection in a domestic cat in Italy - D. D'Annunzio; M. Moreno; T. Tosi; B. Bassi; M. Muscatello; B. Bortolami; D. Drago; F. Fusaro; M. Monne; P. Palumbo; S. Savegnago; T. Terregino; et al. (Journal of Comparative Pathology, 2025)

Wettability and sp2/sp3 ratio effects on supercapacitor performance of N-doped hydrogenated amorphous carbon nanofoam - Subrata Ghosh; Giacomo Pagani; Andrea Macrelli; Alberto Calloni; Gianlorenzo Bussetti; Andrea Lucotti; Matteo Tommasini; Raffaella Suriano; Marco Agozzino; Giorgio Divitini; Yurii P. Ivanov; Veronica Piazza; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Non-cholera Vibrio spp. invasive infections in the summer following May 2023 flood disaster in Romagna, Italy: a case series - I. Zaghi; G. Tebano; E. Vanino; G. Vandi; M. Cricca; V. Sambri; M. Fantini; F. Di Antonio; M. Terzitta; E. Russo; F. Cristini; P. Bassi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

A multi-reference parent nested-association mapping population to dissect the genetics of quantitative traits in durum wheat - Samir Alahmad; Yichen Kang; Eric Dinglasan; Dilani Jambuthenne; Hannah Robinson; Yongfu Tao; Jason A. Able; Jack Christopher; Kai P. Voss-Fels; Filippo M. Bassi; Lee T. Hickey (Genetic Resources and Crop Evolution, 2023)

Effects of artificial light at night on fishes: A synthesis with future research priorities - Arshpreet Bassi; Oliver P. Love; Steven J. Cooke; Theresa R. Warriner; Christopher M. Harris; Christine L. Madliger (Fish and Fisheries, 2022)
Nearly all organisms rely on natural fluctuations of light as cues for synchronizing physiological processes and behavioural actions associated with foraging, growth, sleep and rest, reproduction, and migration. Consequently, although artificial lighting sources have provided a plethora of benefits for humans, they can lead to disruptions for wild organisms. With one quarter of the human population living within 100 km of coastlines, there is great potential for artificial light at night (ALAN) to influence the physiology, behaviour and fitness of fishes. Through a review of the literature ( n = 584 publications focused on the effects of ALAN on individual organisms or ecosystems), we illustrate that most papers have concentrated on terrestrial species (59%) compared with aquatic species (20%) or a mixed approach (21%). Fishes have been underrepresented in comparison with many other taxa such as birds, insects and mammals, representing the focus of less than 8% of taxa‐specific publications. While the number of publications per year focusing on fishes has generally been increasing since the mid‐2000s, there has been a downturn in publication rate in the last few years. To understand where research related to ALAN in fishes has been focused, we partitioned studies into categories and found that publications have mostly concerned behaviour (41.0%), abundance and community structure (24.4%), and physiology (22.8%), while the longer‐term effects on fitness (6.9%) are lacking. We synthesize the research completed in fishes and outline future priorities that will help ascertain the short‐ and long‐term consequences of this relatively novel stressor for fish health and persistence.

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Behaviour of repetitive non-coding DNA in response to heavy metal stress in the protonemata of Funaria hygrometrica - P. Bassi; A. Basile; S. Sorbo (Plant Biosystems, 2015)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Occurrence of TRGV-BJ hybrid gene in SV40-transformed fibroblast cell lines - L. P. G. D’Arce; C. L. Bassi; A. L. Fachin; G. A. S. Passos; E. T. Sakamoto-Hojo (Genetica, 2009)

Bitterness inheritance in apricot (P. armeniaca L.) seeds - P. Negri; D. Bassi; E. Magnanini; M. Rizzo; F. Bartolozzi (Tree Genetics & Genomes, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

Endo/exo-proteolysis in neoplastic progression and metastasis - Abdel-Majid Khatib; Daniel Bassi; Geraldine Siegfried; Andres J. P. Klein-Szanto; L’Houcine Ouafik (Journal of Molecular Medicine, 2005)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)